Tinjauan Yuridis Sosiologis Pelepasan Hak Atas Tanah Adat Menjadi Sertifikat Hak Milik di Distrik Arso Kabupaten Keerom Provinsi Papua - Rama Thimoty Sanjaya; Catur WIdo Haruni; Sholahuddin Al-Fatih (Indonesia Law Reform Journal, 2022)
Part of the Keerom Regency area is a forest owned by the Keerom Indigenous people, in Articles 1 and 2 of the UUPA. the implementation of ulayat rights and similar rights of indigenous peoples, as long as in reality they still exist, must be so that they are in accordance with the national and state interests. The problem in this study is a sociological juridical review of the release of customary land rights into property rights certificates in Keerom Regency. This study raises the problem studied are, First how to release customary land rights to become property rights certificates. Second, what are the obstacles to releasing customary land rights into title certificates? Third, what are the efforts to overcome the obstacles to the Release of Customary Land Rights into Ownership Certificates in Keerom Regency? The research was conducted using a sociological juridical approach. Sources of data, primary data, secondary data, and tertiary flat. Data collection techniques are observation, interviews, and document studies. Based on the results of research and discussion; First, the transfer of rights carried out by indigenous peoples in Keerom Regency are of several kinds, namely; imnaway twa, Ken Baa, maafowor, Mararap Kambiswap, and Kin tuwri Ngkwaf. Second. obstacles, because customary land is not measured on the boundaries of the customary land. Third, to overcome obstacles, the Regional Government and Regency BPN must be active in conducting socialization with the community regarding the importance of registering land rights to ensure legal certainty. The author's suggestion in this study, the local government, and the customary council in Keerom Regency must make a regulation related to customary land so that customary land has legal clarity regarding land ownership.